PENGARUH PEMBELAJARAN STRATEGI PEMECAHAN MASALAH WANKAT TERHADAP KOMPETENSI STRATEGIS MATEMATIKA SISWA - Ni Putu Meina Ayuningsih (LPPM Universitas Dhyana Pura, 2019)
ABSTRACTThis study aims to determine whether the mathematical strategic competencies of students who are taught with a Wankat problem solving strategy are better or not from the mathematical strategic competencies of students who get conventional learning. This type of research is a quasi experiment with a posttest only control group design. The sampling technique in this study was a cluster sampling randomly selected class that was used as the experimental group and the control group. The data in this study are students' mathematical strategic competency data collected by mathematical strategic competency tests. The data obtained were analyzed descriptively based on the one-tailed t-test at the 5% significance level for hypothesis 1. The results showed that the mathematics strategic competencies of students who were given the problem solving strategy learning were better than the mathematical strategic competencies of students who received conventional learning. In other words, there is a positive influence on learning the problem solving strategy for students towards students' mathematical strategic competencies.Keywords: Wankat problem solving strategy, mathematical strategic competence, quasi experimentABSTRAKPenelitian ini bertujuan untuk mengetahui apakah kompetensi strategis matematika siswa yang dibelajarkan dengan strategi pemecahan masalah Wankat lebih baik atau tidak dari kompetensi strategis matematika siswa yang mendapat pembelajaran konvensional. Jenis penelitian ini adalah quasi experiment dengan rancangan posttest only control group design. Teknik pengambilan sampel dalam penelitian ini adalah cluster sampling yang dipilih secara random kelas yang digunakan sebagai kelompok eksperimen dan kelompok kontrol. Data dalam penelitian ini adalah data kompetensi strategis matematika siswa yang dikumpulkan dengan tes kompetensi strategis matematika. Data yang diperoleh dianalisis secara deskriptif berdasarkan uji-t satu ekor pada taraf signifikansi 5% untuk hipotesis 1. Hasil penelitian menunjukkan bahwa kompetensi strategis matematika siswa yang diberi pembelajaran strategi pemecahan masalah Wankat lebih baik daripada kompetensi strategis matematika siswa yang mendapat pembelajaran konvensional. Dengan kata lain ada pengaruh positif pembelajaran strategi pemecahan masalah Wankat terhadap kompetensi strategis matematika siswa.Kata kunci: strategi pemecahan masalah Wankat, kompetensi strategis matematika, quasi experiment.